Assessment of a major shore-based marine recreational fishery in the southwest Atlantic, Argentina - Llompart, Facundo Manuel (2012)
This work provides, based on data from roving creel surveys, the first quantitative analysis for a main recreational fishery of the southwestern Atlantic coast. Anglers interviewed were willing to accept minimum size limits but mostly did not approve the maximum daily catch, despite the fact that they considered that the fishery quality was decreasing. Angler profile differed among months but the avidity effect was negligible. Fishing effort was highest during January, with the greatest total catch per unit effort (CPUE) in November and the highest total catch in December. Twelve species were caught, with Cynoscion guatucupa and Micropogonias furnieri accounting for 80% of the harvest. The average lengths for both species were larger than their size at first maturity. Mean (9SD) CPUE values (1.2890.59 fish/angler/h) and total harvest were high compared with those of other recreational fisheries in the Southern Hemisphere. Some specific fishing-management guidelines are proposed to promote good angling practices and sustainable long-term use of the resource.